2016
DOI: 10.1038/srep21145
|View full text |Cite
|
Sign up to set email alerts
|

Icariin displays anticancer activity against human esophageal cancer cells via regulating endoplasmic reticulum stress-mediated apoptotic signaling

Abstract: In this study, we investigated the antitumor activity of icariin (ICA) in human esophageal squamous cell carcinoma (ESCC) in vitro and in vivo and explored the role of endoplasmic reticulum stress (ERS) signaling in this activity. ICA treatment resulted in a dose- and time-dependent decrease in the viability of human EC109 and TE1 ESCCs. Additionally, ICA exhibited strong antitumor activity, as evidenced by reductions in cell migration, adhesion, and intracellular glutathione (GSH) levels and by increases in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 63 publications
0
48
0
Order By: Relevance
“…ERS pathway is also reported to participate in the malignancy of diverse cancers, such as the metastasis of breast cancer [34,35], the poor progression of gastric carcinoma [36] as well as anti-cancer drug resistance of lung cancer cells and ovarian carcinoma cells [37]. Moreover, another study also demonstrates Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry that icariin exerts anti-tumor activity by upregulating the expression of ERS -related molecules (GRP78, CHOP, p-PERK and p-eIF2a), resulting in the inhibition of cell migration, adhesion and increase in apoptosis [38]. In the current study, we demonstrated that miR-410 inhibition can suppress the expression of ERS-related genes, including CHOP, GRP94, Bip and the phosphorylation level of eIF2α.…”
Section: Discussionmentioning
confidence: 94%
“…ERS pathway is also reported to participate in the malignancy of diverse cancers, such as the metastasis of breast cancer [34,35], the poor progression of gastric carcinoma [36] as well as anti-cancer drug resistance of lung cancer cells and ovarian carcinoma cells [37]. Moreover, another study also demonstrates Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry that icariin exerts anti-tumor activity by upregulating the expression of ERS -related molecules (GRP78, CHOP, p-PERK and p-eIF2a), resulting in the inhibition of cell migration, adhesion and increase in apoptosis [38]. In the current study, we demonstrated that miR-410 inhibition can suppress the expression of ERS-related genes, including CHOP, GRP94, Bip and the phosphorylation level of eIF2α.…”
Section: Discussionmentioning
confidence: 94%
“…Metastatic progression is a complex, multi-step process wherein tumor cells undergo changes in their migratory, invasive, proliferative, phenotypic, and angiogenic properties that enable them to expand and spread to distant metastatic sites within affected individuals. [21][22][23] Both invasion and migration are key components of the metastatic process. 12 A number of studies have explored the ability of ICA II to modulate the invasivity and migratory capabilities of lung, gastric, and esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) is an important organelle that is responsible for the folding, modification and transport of proteins in cells . Recent studies have suggested that ER stress plays a key role in the progression of tumors . Under normal conditions, the ER environment is in the stable, steady state.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recent studies have suggested that ER stress plays a key role in the progression of tumors. [10][11][12] Under normal conditions, the ER environment is in the stable, steady state. Once the steady state is destroyed, the misfolded or unfolded proteins accumulate and then induce endoplasmic reticulum stress (ERS).…”
Section: Introductionmentioning
confidence: 99%